4- Women, NEPAD and Nation Building: Revisiting a Dying Debate - Okeke, Philomina E.; Onu, Godwin (African Sociological Review, 2006)
This article is not a contribution to the usual critiques levelled against the New Partnership for Africa’s Development (NEPAD) such as the credentials of its architects, the structural capacity of receiving African nations, the benefits of trade and investment proposals over inherent conditionalities for development aid. Rather, the analysis here revisits an earlier but short flurry of debates on the gender implications of this plan. NEPAD has been debated and assessed in many forums. Indeed, the scholarly discourse appears to have shifted to the prospects of a crucial pillar in the plan – the Peer Review Mechanism (PRM). In accentuating the need for a continuing debate on the substance of NEPAD’s plan for gender inclusion in social governance, this article argues that the document, similar to its predecessors, remains incomplete, the usefulness of expert evaluations insufficient, as long as it refuses to confront the Women Question in concrete terms.